An Integrated Multi-Risk Assessment for Floods and Drought in the Marrakech-Safi Region (Morocco) - Cotti, Davide; Harb, Mostapha; Hadri, Abdessamad; Aboufirass, Mohammed; Chaham, Khalid Rkha; Libertino, Andrea; Campo, Lorenzo; Trasforini, Eva; Krätzschmar, Elke; Bellert, Felicitas; Hagenlocher, Michael (Frontiers in Water, 2022)
Multi-risk assessments are being increasingly proposed as a tool to effectively support policy-makers in reducing impacts from natural hazards. The complexity of multi-risk requires assessment approaches capable of capturing multiple components of risk (e.g., different hazards, exposed elements, and dimensions of vulnerability) in a coherent frame of reference, while at the same time providing an intuitive entry point to allow participation of relevant stakeholders. Contributing to the emerging multi-risk literature, we carried out a multi-risk assessment for the Marrakech-Safi region (Morocco)—an important economic and demographic hub in the country that is prone to multiple natural hazards, most notably floods and droughts. Through multiple consultations with local experts and stakeholders, a multi-risk assessment framework was constructed based on a set of single-risks related to flood and drought hazards. For each risk, spatial analysis was employed to assess the hazard exposure component of multi-risk, while a set of vulnerability indicators and stakeholder-informed weights were used to construct a composite indicator of vulnerability at the municipal level. For each municipality, the set of indicators and weights contributing to the composite indicator was designed to be dependent on the combination of risks the municipality is actually confronted with. The two components were aggregated using a risk matrix approach. Results show a significant proportion of municipalities (28%) reaching very high multi-risk levels, with a large influence of drought-related risks, and a prominent contribution of the vulnerability component on the overall multi-risk results. While the approach has allowed the exploration of the spatial variability of multi-risk in its multiple sub-components and the incorporation of stakeholders' opinions at different levels, more research is needed to explore how best to disentangle the complexity of the final multi-risk product into a tool capable of informing policy-makers in the identification of entry points for effective disaster risk governance.